Statement by the Managing Director on the Independent Evaluation Office Report on IMF Collaboration with the World Bank on Macro-Structural Issues; June 15, 2020. (Policy Papers; Policy Paper ;, 2020)
Statement by the Managing Director on the Independent Evaluation Office Report on IMF Collaboration with the World Bank on Macro-Structural Issues.